Does Surgical Margin Impact Recurrence in Noninvasive Intraductal Papillary Mucinous Neoplasms?: A Multi-institutional Study. Issue 3 (September 2018) - Dhar, Vikrom K.; Merchant, Nipun B.; Patel, Sameer H.; Edwards, Michael J.; Wima, Koffi; Imbus, Joseph; Abbott, Daniel E.; Weber, Sharon M.; Louie, Raphael; Kim, Hong J.; Martin, Robert C. G.; Scoggins, Charles R.; et al.
Abstract : Objective: The relevance of margin positivity on recurrence after resection of intraductal papillary mucinous neoplasms (IPMNs) is poorly defined and represents one reason controversy remains regarding optimal surveillance recommendations. Methods: Patients undergoing surgery for noninvasive IPMN at 8 academic medical centers from the Central Pancreas Consortium were analyzed. A positive margin was defined as presence of IPMN or pancreatic intraepithelial neoplasia. Results: Five hundred two patients underwent surgery for IPMN; 330 (66%) did not have invasive cancer on final pathology and form the study cohort. Of these, 20% harbored high grade dysplasia. A positive margin was found in 20% of cases and was associated with multifocal disease ( P = 0.02). The majority of positive margins were associated with low grade dysplasia. At a median follow-up of 36 months, 34 (10.3%) patients recurred, with 6.7% developing recurrent cystic disease and 3.6% developing invasive cancer. On multivariate analysis, margin positivity was not associated with recurrence of either IPMN or invasive cancer ( P > 0.05). No association between margin status and development of recurrence at the margin was found. Only 6% of recurrences developed at the resection margin and median time to recurrence was 22 months. Of note, 18% of recurrences occurred > 5 years following surgery. Conclusion: Margin positivity after resection for noninvasive IPMNs is primarily due to low grade dysplasia and is not associated with developing recurrence in the remnant pancreas or at the resection margin. Long-term surveillance is required for all patients, as a significant number of recurrences developed over 5 years after the index operation.